Identifying Students' Interest in Inheritance of Traits and Breeding of Living Things to Support ESD - Dewanti*, Amanda Putri; Pertiwi, Faninda Novika (Universitas Syiah Kuala, 2024)
The genetic strategy, namely the inheritance of traits and breeding of living things, is a complex material at the secondary school level. The difficulty of understanding the material is due to the absence of discussion of this material at the elementary school level and the use of science terms that students rarely hear. This study aims to determine students' interest in the material inheritance of traits and reproduction of living things, methods and learning resources used, and students' ability to identify the material inheritance of traits and reproduction of living things using indicators of reading ability. The method used in this research is quantitative-qualitative to see junior high school students' interest and identification results. Researchers used data from statistical analysis and interviews with students. Data analysis was done by reducing, presenting, and drawing conclusions. The results showed that interactive and varied learning resources, methods, and models can influence students' interests and learning outcomes. Interactive learning models can improve student learning outcomes in the material of inheritance of traits and breeding of living things and help students understand the concept of sustainable development